Report of Land Use Alternatives 1977 - Joe Garrett::::::; Tom Laubacher::::::; Ted Grandsen::::::; Alfred Nunes:::::: (1977)
A report provided by the Regional Land Use Program discussing possible development alternatives based on possible population growth.